2020
DOI: 10.4314/sajas.v50i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing diets for broilers that are low in crude protein and amino acids with protease

Abstract: The study evaluated supplementation of broiler diets with a protease enzyme. Six hundred Ross 308 female broiler chicks were acquired at one day of age and randomly distributed to three treatments with five replicates of 40 chicks each. The experimental treatements consisted of i) a positive control diet with normal levels of crude protein, digestible lysine and digestible sulphur containing amino acids (PC); ii) a negative diet with reduced levels of crude protein, digestible lysine and digestible sulphur con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Soybean meal is considered highly digestible for poultry, but there are still possibilities to improve its nutritional value. Several studies have shown that the addition of proteolytic enzymes can maximize protein digestibility and metabolizable energy in high-performance broiler diets [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Therefore, analyzing the interaction between the origin of soybean meal and the addition of exogenous enzymes is required.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean meal is considered highly digestible for poultry, but there are still possibilities to improve its nutritional value. Several studies have shown that the addition of proteolytic enzymes can maximize protein digestibility and metabolizable energy in high-performance broiler diets [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Therefore, analyzing the interaction between the origin of soybean meal and the addition of exogenous enzymes is required.…”
Section: Discussionmentioning
confidence: 99%
“…Under coccidial infection, the dietary supplementation of protease greatly improves the body weight of broilers, alleviating the adverse effects of the disease on growth (Peek et al 2009). Broilers fed with protease show an improvement in carcass yield without alteration in fat deposition rates (Law et al 2017), and the crude protein content of meat increases (Sarica et al 2020). Xu et al (2017) reported that diets supplemented with protease had increased the breast meat yield of broilers.…”
mentioning
confidence: 99%